Clinical Characterization of Patients with Chronic Spontaneous Urticaria according to Anti-TPO IgE Levels - Jorge Sánchez; Andres Sánchez; Ricardo Cardona (Journal of Immunology Research, 2019)
Background. Chronic spontaneous urticaria (CSU) is a heterogeneous disease with some frequent comorbidities like autoimmune diseases, drug reactions, and inducible urticaria. IgE antibodies against thyroid peroxidase (anti-TPO IgE) could be associated with some of these clinical characteristics. Objective. To explore the clinical characteristics of CSU patients, according to the presence of anti-TPO IgE in serum. Methods. Anti-TPO IgE levels were measured during the clinical control period (Urticaria Activity Score, 0 point) and exacerbation period (≥3 points) in 100 CSU patients. Patients with self-reported exacerbation of skin involvement by foods, nonsteroidal anti-inflammatory drugs (NSAIDs), and physical triggers underwent controlled challenge tests. Results. We identified 2 groups of patients: (1) patients with anti-TPO IgE during the clinical control period or during an exacerbation, who had a higher frequency of atopy, asthma, and positive challenge test results with NSAIDs and (2) patients without anti-TPO IgE during any period, who had a higher frequency of positive challenge test results for inducible urticaria. Among the first group (anti-TPO IgE at any point), we identified 3 subgroups: patients with anti-TPO IgE during the clinical control period (n=12); patients with anti-TPO IgE during the clinical control period and significantly increased levels during an urticaria exacerbation (n=18); and patients with anti-TPO IgE only during an exacerbation (n=13). None of the patients with self-reported food reactions had a positive challenge test result. Conclusion. Anti-TPO IgE is a useful biomarker for differentiating between clinical phenotypes of patients with CSU. Elevation of anti-TPO IgE during exacerbation periods supports an association between this autoantibody and the pathogenesis of urticaria.